Repurposing pitavastatin and atorvastatin to overcome chemoresistance of metastatic colorectal cancer under high glucose conditions - Wei-Ming Cheng; Po-Chen Li; Minh Tran-Binh Nguyen; Yu-Teng Lin; Yu-Tang Huang; Tai-Shan Cheng; Thi-Huong Nguyen; Thu-Ha Tran; Tzu-Yi Huang; Thu-Huyen Hoang; Sin-Yu Chen; Yu-Chieh Chu; et al. (Cancer Cell International)
Abstract Background Colorectal cancer (CRC) poses a significant clinical challenge because of drug resistance, which can adversely impact patient outcomes. Recent research has shown that abnormalities within the tumor microenvironment, especially hyperglycemia, play a crucial role in promoting metastasis and chemoresistance, and thereby determine the overall prognosis of patients with advanced CRC. Methods This study employs data mining and consensus molecular subtype (CMS) techniques to identify pitavastatin and atorvastatin as potential agents for targeting high glucose-induced drug resistance in advanced CRC cells. CRC cells maintained under either low or high glucose conditions were established and utilized to assess the cytotoxic effects of pitavastatin and atorvastatin, both with and without 5-fluorouracil (5-FU). CRC 3D spheroids cultured were also included to demonstrate the anti-drug resistance of pitavastatin and atorvastatin. Results A bioinformatics analysis identified pitavastatin and atorvastatin as promising drug candidates. The CMS4 CRC cell line SW480 (SW480-HG) was established and cultured under high glucose conditions to simulate hyperglycemia-induced drug resistance and metastasis in CRC patients. Pitavastatin and atorvastatin could inhibit cell proliferation and 3D spheroid formation of CMS4 CRC cells under high glucose conditions. In addition, both pitavastatin and atorvastatin can synergistically promote the 5-FU-mediated cytotoxic effect and inhibit the growth of 5-FU-resistant CRC cells. Mechanistically, pitavastatin and atorvastatin can induce apoptosis and synergistically promote the 5-FU-mediated cytotoxic effect by activating autophagy, as well as the PERK/ATF4/CHOP signaling pathway while decreasing YAP expression. Conclusion This study highlights the biomarker-guided precision medicine strategy for drug repurposing. Pitavastatin and atorvastatin could be used to assist in the treatment of advanced CRC, particularly with CMS4 subtype CRC patients who also suffer from hyperglycemia. Pitavastatin, with an achievable dosage used for clinical interventions, is highly recommended for a novel CRC therapeutic strategy.